Evaluation of Li-TMS as an intervention to enhance cognitive performance in university students - Raúl Sampieri Cabrera; Alan Oviedo; Erandi Pérez (Journal of Neuroeducation)
Background:The present study evaluated the impact of low-intensity transcranial magnetic stimulation (Li-TMS) on the cognitive performance of university students. Given the increasing interest in non-invasive brain stimulation techniques to enhance cognitive functions, this study aims to explore the efficacy of Li-TMS using the Digit Symbol Substitution Test (DSST) as a measure of cognitive performance. Methods: The sample included 30 participants, who were randomly divided into two groups: an experimental group and a control group. The experimental group received daily Li-TMS sessions for 10 days. In contrast, the control group received sham low-intensity sessions under the same temporal protocol to control for placebo effects. The DSST was administered to all participants before and after the intervention to assess changes in cognitive performance. Results: The results demonstrated a significant improvement in DSST scores in the experimental group compared to the control group. This finding suggests that Li-TMS can effectively enhance specific cognitive skills in a young and healthy population. Conclusion: Li-TMS appears to be a promising tool for cognitive enhancement, with potential applications in educational and professional settings. These findings support the utility of Li-TMS as a cognitive training intervention, offering a non-invasive method to improve cognitive functions in young adults. Further research is warranted to explore the long-term effects and underlying mechanisms of Li-TMS on cognitive performance.